Neuropsychological conditions across the lifespan - Donders, Jacobus; Hunter, Scott J. (Cambridge : Cambridge University Press, 2018)
This unique analysis of neuropsychological conditions provides readers with a review of both pediatric and adult presentations in one convenient place. Covering the most common disorders encountered in clinical practice, including those specific to the extremes of the age spectrum, this book provides dedicated chapters on: * Preterm and low weight birth * Spina bifida myelomeningocele * Autism spectrum disorder * Intellectual disability * Fetal alcohol spectrum disorders * Attention-deficit/hyperactivity disorder * Learning disability * Traumatic brain injury * Cancer * Epilepsy * Human immunodeficiency virus * Multiple sclerosis * Stroke * Dementia Each chapter provides evidence-based guidelines that can be readily applied to daily practice.
Machine generated contents note: 1. Preterm and Low Birth Weight Birth Julia Jaekel and Megan Scott; 2. Spina Bifida Myelomeningocele Colleen F. Bechtel Driscoll, Grayson N. Holmbeck, Kathy Zebracki ,T. Andrew Zabel, Alexa Stern, Jaclyn Lennon Papadakis and Diana Ohanian ; 3. Autism Spectrum Disorder (ASD) Julie M. Wolf, Marianne Barton, and Roger Jou; 4. Neuropsychological Conditions Across the Lifespan Intellectual Disability Syndromes, Kelly Janke and Lisa Jacola; 5. Fetal Alcohol Spectrum Disorders, Israel M. Gross, and Douglas Bodin; 6. Neuropsychological Conditions Across the Lifespan: Attention-Deficit/Hyperactivity Disorder, J.G. Fine, D.J. Marks, D. Wexler, V.M Dahl, and E.P. Horn; 7. Learning Disabilities, Richard Boada, Robin L. Peterson and Robert L. Mapou; 8. Traumatic Brain Injury, Tresa Roebuck-Spencer, Naddley De;sire;, and Miriam Beauchamp; 9. Cancer, Iris Paltin, Marsha Gragert, Tanya Antonini, and Chad Noggle; 10. Epilepsy, Julie Janecek, Klajdi Puka, Evan Schulze and Mary Lou Smith ; 11. Neuropsychological Conditions Across the Lifespan: Human Immunodeficiency Virus, Steven Paul Woods, Kelli L. Sullivan, Sharon Nichols, and Scott J. Hunter; 12. Multiple Sclerosis, Lana Harder, Julie A. Bobholz, and William S. MacAllister; 13. Stroke, Robyn Westmacott, Angela Deotto, and David Nyenhuis; 14. Dementia, Laura Lacritz, Heidi Rossetti, & Christian LoBue .
Title from publisher's bibliographic system (viewed on 01 Aug 2018).
Keywords: Central nervous system -- Diseases